Avoiding unfavorable results in postburn contracture hand - Sameek Bhattacharya (Indian Journal of Plastic Surgery)
Deformities of the hands are a fairly common sequel of burn especially in the developing world. This is because of high incidence of burns, limited access to standard treatment and rehabilitation. The best outcome of a burnt hand is when deformities are prevented from developing. A good functional result is possible when due consideration is paid to hands during resuscitation, excisional surgery, reconstructive surgery and physiotherapy. The post-burns deformities of hand develop due direct thermal damage or secondary to intrinsic minus position due to oedema or vascular insufficiency. During the acute phase the concerns are, maintenance circulation minimize oedema prevent unphysiological positioning and wound closure with autogenous tissue as soon as possible. The rehabilitation program during the acute phase starts from day one and goes on till the hand has healed and has regained full range of motion. Full blown hand contractures are challenging to correct and become more difficult as time passes. Long-standing cases often land up with attenuation of extensor apparatus leading to swan neck and boutonniere deformity, muscle shortening and bony ankylosis. The major and most common pitfall after contracture release is relapse. The treatment protocol of contracture is solely directed towards countering this tendency. This article aims to guide a surgeon in obtaining optimal hand function and avoid pit falls at different stages of management of hand burns. The reasons of an unfavourable outcome of a burnt hand are possible lack of optimal care in the acute phase, while planning and performing reconstructive procedure and during aftercare and rehabilitation.